2001
DOI: 10.1055/s-2001-19139
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Postmenopausal Hormone Replacement Therapy and Oral Contraceptives on the Endogenous Estradiol Metabolism

Abstract: The estradiol metabolism may be of clinical relevance in the pathophysiology of various diseases; the increase in D-ring metabolites over A-ring metabolites in breast cancer patients is of special interest. Since estrogen therapy has been blamed for increasing the risk of breast cancer, the effects of hormonal replacement therapy (HRT) and oral contraception were investigated on the ratio of the main D-ring metabolite, 16alpha-hydroxyestrone (16-OHE1), to the main A-ring metabolite, 2-hydroxyestrone (2-OHE1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…The methods for urine collection always involved the addition of ascorbic acid for preservation purposes, but the time of urine collection varied: a spot urine collection was used in 10 studies [4, 49, 52, 56, 57, 69, 70, 75, 77, 85, 95], while 18 studies [5, 6, 54, 55, 58-64, 68, 74, 76, 78-81, 87-94, 99] reported on overnight urine collection. The remaining studies included 12, 24, 48 or 72 urine collection protocols.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for urine collection always involved the addition of ascorbic acid for preservation purposes, but the time of urine collection varied: a spot urine collection was used in 10 studies [4, 49, 52, 56, 57, 69, 70, 75, 77, 85, 95], while 18 studies [5, 6, 54, 55, 58-64, 68, 74, 76, 78-81, 87-94, 99] reported on overnight urine collection. The remaining studies included 12, 24, 48 or 72 urine collection protocols.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the studies that addressed postmenopausal hormone usage, three did not report a significant impact on the 2/16 ratio [52, 78, 79] while another study observed significant changes in the ratio in smokers only [98]. …”
Section: Resultsmentioning
confidence: 99%
“…Evidence exists that estrogen metabolites can be modified by human behaviors such as smoking [36][37][38], hormonal contraceptives [39,40], body fat [41][42][43], and diet [44][45][46]. Physical activity is a modifiable human behavior that may alter estrogen metabolism but research is limited.…”
Section: Introductionmentioning
confidence: 99%
“…We have also investigated the effects of different contraceptives because similar potential genotoxic metabolites have been described using ethinyl estradiol (78). However, it seems that proliferative mechanisms are more important, although ethinyl estradiol showed much lower effects compared to estradiol (see section on 'Different effects of estrogens on proliferation mechanisms').…”
Section: Carcinogenicity By Genotoxic Estrogen Metabolites Potential mentioning
confidence: 98%